Gangguan siklus menstruasi kaitannya dengan asupan zat gizi pada remaja vegetarian - Wahyuni, Yulia; Dewi, Ratna (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2018)
Background : Adolescence is a period that is still experiencing growth, especially the reproductive system with menstruation is supported adequate nutrients. Objective : The aim of this study was to determined Â the association of the sufï¬cient of protein, vitamin B12, vitamin C, iron intake, nutritional status with cycle mestruasi on vegetarian adolescent at IVS Jakarta 2017. Method : This design research was observation analytic with cross sectional approach. Sampling technique were used total sampling. The technique of data collection were used menstrual cycle questionnaire, Semi Quantitatif Food Frequency, food model, nutrisurvey, BMI for age. Results : There was 35,71 % respondents have an oligomenorrhea. Food intake (protein, vitamin B12, vitamin C, iron) were inadequate, while vitamin C was intake adequate. Based on statistical analysis of Spearman Rank test, There were significant relation between sufficient intake of protein (p =0,001), sufficient intake of vitamin C (p = 0,003) sufficient intake of iron (p = 0,001) with menstrual cycle. There was no significant relationship between vitamin B12 intake (P = 0.34) nutritional status (P = 0.54) with menstrual cycle. Conclusion : food intake (protein, iron, vitamin C) associated with the menstrual cycle. vitamin B12 intake and nutritional status not associatied with the menstrual cycle.